The produce of Matang mangrove in Kuala Sepetang, Perak - Mohd Nazip, Muhammad Nadzim; Abdullah, Syazwani; Rais, Mohd Rafsan; Mat Anuar, Muhammad Shahedie (2012)
Mangrove forests grow near the coast and are periodically inundated by sea water. It plays an important role to prevent coastal erosion along the coast. A study site was conducted in Matang Mangrove Forest Reserve at Kuala Sepetang, Perak. The objectives of this research are to study the mangrove management and the contribution of the mangrove species to socio-economic. All the information from the Perak State Forestry Department of which includes the mangrove management and their contribution to the community are collected. The data obtained in the study were analyzed. The results show that Matang Mangroves Forest Reserve is proven as the best management facility as it balanced the felling and growing of the mangrove species. In area 1 of the Matang Mangrove area location 1,3,5,7,11 is considered loss as of area 2,4,6,8,9,10,12 is considered growth because using remote sensing technology, in the year 2007. With this process, the forest reserve is able to supply mangrove continuously. Furthermore, the socio-economic development of the Matang resident seems to be prospective as the fisheries industry has the highest annual net-income for the local with a total RM 200 million and as the lowest RM 1560 is the employment sector. The finding of the study was preferred that mangrove species is suitable to be planted because it is give more beneficial either to protection and industry.